Project-Based Learning and Problem-Based Learning Models in Critical and Creative Students - Suradika, A.; Dewi, H. I.; Nasution, M. I. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2023)
This research is experimental research with a 2 x 2 factorial design involving students in the critical and creative categories. Data collection used a description test instrument. Data were analyzed inferentially by hypothesis testing ANACOVA comparison. Problem-Based Learning (PBL) directs students to learn, directs individual and group investigations, generates and performs work, and assesses the problem-solving process. While the syntaxes for Project-Based Learning (PjBL) are starting learning with essential questions, designing a plan for the project, creating the schedule, monitoring students and project progress, assessing the outcome, and evaluating. This study concludes that there is no difference in chemistry learning outcomes between students who are taught using PBL and PjBL, and students who are critical and creative. For syntax, there are similarities in the activities of critical and creative students, at the PjBL stage, in designing a project and evaluating a product, and at the PBL stage, in guiding individual investigations and developing and presenting results.